Stigma and social control - Lawrence E. Blume (Institute for Advanced Studies (IHS), 2002)
Social interactions provide a set of incentives for regulating individual behavior. Chief among these is stigma, the status loss and discrimination that results from the display of stigmatized attributes or behaviors. The stigmatization of behavior is the enforcement mechanism behind social norms. This paper models the incentive effects of stigmatization in the context of undertaking criminal acts. Stigma is a flow cost of uncertain duration which varies negatively with the number of stigmatized individuals. Criminal opportunities arrive randomly and an equilibrium model describes the conditions under which each individual chooses the behavior that, if detected, is stigmatized. The comparative static analysis of stigma costs differs from that of conventional penalties. One surprising result with important policy implications is that stigma costs of long duration will lead to increased crime rates.
Keywords: C73; Z13; 330; crime; stigma; social norms; Kriminalitätsökonomik; Spieltheorie; Theorie; Soziale Ungleichheit; Soziale Norm; Soziale Beziehungen